Targeting Sphingolipids for Cancer Therapy - Companioni, Osmel; Mir, Cristina; Garcia-Mayea, Yoelsis; LLeonart, Matilde E. (Frontiers in Oncology, 2021)
Sphingolipids are an extensive class of lipids with different functions in the cell, ranging from proliferation to cell death. Sphingolipids are modified in multiple cancers and are responsible for tumor proliferation, progression, and metastasis. Several inhibitors or activators of sphingolipid signaling, such as fenretinide, safingol, ABC294640, ceramide nanoliposomes (CNLs), SKI-II, α-galactosylceramide, fingolimod, and sonepcizumab, have been described. The objective of this review was to analyze the results from preclinical and clinical trials of these drugs for the treatment of cancer. Sphingolipid-targeting drugs have been tested alone or in combination with chemotherapy, exhibiting antitumor activity alone and in synergism with chemotherapy in vitro and in vivo. As a consequence of treatments, the most frequent mechanism of cell death is apoptosis, followed by autophagy. Aslthough all these drugs have produced good results in preclinical studies of multiple cancers, the outcomes of clinical trials have not been similar. The most effective drugs are fenretinide and α-galactosylceramide (α-GalCer). In contrast, minor adverse effects restricted to a few subjects and hepatic toxicity have been observed in clinical trials of ABC294640 and safingol, respectively. In the case of CNLs, SKI-II, fingolimod and sonepcizumab there are some limitations and absence of enough clinical studies to demonstrate a benefit. The effectiveness or lack of a major therapeutic effect of sphingolipid modulation by some drugs as a cancer therapy and other aspects related to their mechanism of action are discussed in this review.